2016
DOI: 10.1007/s00213-016-4229-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partial dopamine depletion on cognitive flexibility in BDNF heterozygous mice

Abstract: Rationale Cognitive flexibility is a key component of executive function and is disrupted in major psychiatric disorders. Brain-derived neurotrophic factor (BDNF) exerts neuromodulatory effects on synaptic transmission and cognitive/affective behaviors. However the causal mechanisms linking BDNF hypofunction with executive deficits are not well understood. Objectives Here, we assessed the consequences of BDNF hemizygosity on cognitive flexibility in mice performing an operant conditioning task. As dopaminerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 86 publications
(104 reference statements)
2
14
0
Order By: Relevance
“…The main finding of the present study was that plasma levels of catecholamine metabolites were not associated with serum BDNF levels, even though catecholamine might influence BDNF synthesis and secretion in the brain ( 21 ) and BDNF might play an important role in the synthesis and/or secretion of catecholamine ( 22 ). We have previously reported a negative correlation between plasma MHPG and serum BDNF in healthy workers ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 55%
“…The main finding of the present study was that plasma levels of catecholamine metabolites were not associated with serum BDNF levels, even though catecholamine might influence BDNF synthesis and secretion in the brain ( 21 ) and BDNF might play an important role in the synthesis and/or secretion of catecholamine ( 22 ). We have previously reported a negative correlation between plasma MHPG and serum BDNF in healthy workers ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 55%
“…Conversely, reducing DA levels by pharmacological depletion of DA neurotransmission in the DMS impairs odor-guided reversal learning, without affecting initial discrimination learning (O'Neill and Brown, 2007). A similar depletion targeting more largely the DS induces a deficit in the acquisition of a visual discrimination task, and alters the acquisition of a new rule in a set-shifting task in mice (Parikh et al, 2016). Another study using DA-deficient mice showed similar results in a water U-maze paradigm where mice had to shift from an initially acquired escape strategy to a new strategy (Darvas and Palmiter, 2011).…”
Section: Iii3 Dopaminergic Afferencesmentioning
confidence: 99%
“…The functional link between reduced BDNF signaling and GABA deficits across psychiatric disorders also suggests it may contribute to common behavioral endophenotypes across disorders. Cognitive function is primarily controlled via corticolimbic mechanisms, in part through regulation of excitatory and inhibitory neurotransmission (Kellendonk et al, 2009;Caballero and Tseng, 2016), and a number of synaptic modulators have been implicated in these processes, including BDNF and α5-GABA A R. Notably, reduced expression or activity of BDNF or α5-GABA A R in mice commonly manifests as cognitive inflexibility and sensorimotor gating deficits (Hauser et al, 2005;Engin et al, 2013;Manning and van den Buuse, 2013;Parikh et al, 2016). This suggests these molecules represent a network of regulators underlying cognitive processes commonly affected across psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Bdnf +/mice were recently shown to exhibit reduced cognitive flexibility in a visual discrimination task (Parikh et al, 2016). To further address deficits in cognitive flexibility in Bdnf +/mice, we used a rule shifting paradigm (Bissonette et al, 2008;Cho et al, 2015), in which mice were initially trained to associate food reward with a specific stimulus (i.e., either an odor or a digging medium) and subsequently evaluated for cognitive flexibility by changing the type of stimulus that predicts the reward (Figure 2D).…”
Section: Elevated P62 Expression In Bdnf +/Mice Mediates Behavioral Dmentioning
confidence: 99%
See 1 more Smart Citation